The streets of Panic Park - Stine, R. L. (New York : Scholastic, 2009)
Luke and Lizzie try to escape Horrorland by going through Panic Park where they must team up with an old foe and face their fears in order to outsmart the Menace.
4.4
5-8
Keywords: Amusement parks -- Juvenile fiction; Good and evil -- Juvenile fiction; Secrecy -- Juvenile fiction; Amusement parks -- Fiction; Good and evil -- Fiction; Horror stories; Secrets -- Fiction; Amusement parks -- Fiction; Good and evil -- Fiction; Horror fiction; Secrecy -- Fiction; Horror fiction